INNOVATION AND SUSTAINABILITY AT THE UNIVERSITY – ENTERPRISE - Ríos Delgado, Teresa Jesús (2014)
This research has been developed in order to obtain a correlation between innovation and sustainability at the university-enterprise, having as an objective to define a relationship between both constructs, because it is essential to settle up a management, which must design and carry through (educational) process and products (university´s goals) by means of innovation as a management strategy. This study is descriptive, explicative and a documental research. As main conclusion it was settled that new processes of shared learnings by several students’ communities apart by distance and the enterprises’ must be founded in proposals in order to develop research between students and enterprises using new technology.